2022
DOI: 10.12688/hrbopenres.13483.2
|View full text |Cite
|
Sign up to set email alerts
|

Quality care process metrics for nurses working in general practice, mapping the evidence: a scoping review protocol

Abstract: Background: Irish general practice nursing roles have developed and grown exponentially in response to changing policy, clinical and workforce demands, this is reflective of international primary healthcare nursing trends. However, as nursing care in general practice advances, comprehensive evaluation of the general practice nurse (GPN) role has not been undertaken. Therefore, processes which enable robust data collection to assess the role and facilitate development of services are required. Nursing quality c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Recent research involving a survey of Practice Nurses and GPs in one county found that the large majority considered an expanded role for practice nurses to be a high priority 6 . Further research is ongoing and aims to quantify the provision of quality Nursing care in Irish General Practice 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research involving a survey of Practice Nurses and GPs in one county found that the large majority considered an expanded role for practice nurses to be a high priority 6 . Further research is ongoing and aims to quantify the provision of quality Nursing care in Irish General Practice 45 .…”
Section: Discussionmentioning
confidence: 99%